Adhesive curing through low-voltage activation - Ping, Jianfeng (2017)
Instant curing adhesives typically fall within three categories, being activated by either light (photocuring), heat (thermocuring) or chemical means. These curing strategies limit applications to specific substrates and can only be activated under certain conditions. Here we present the development of an instant curing adhesive through low-voltage activation. The electrocuring adhesive is synthesized by grafting carbene precursors on polyamidoamine dendrimers and dissolving in aqueous solvents to form viscous gels. The electrocuring adhesives are activated at −2 V versus Ag/AgCl, allowing tunable crosslinking within the dendrimer matrix and on both electrode surfaces. As the applied voltage discontinued, crosslinking immediately terminated. Thus, crosslinking initiation and propagation are observed to be voltage and time dependent, enabling tuning of both material properties and adhesive strength. The electrocuring adhesive has immediate implications in manufacturing and development of implantable bioadhesives.